The freestyle stentless bioprosthesis in more than 1000 patients: A single-center experience over 10 years - Ennker, J.; Ennker, I.; Albert, A.; Rosendahl, U.; Bauer, S.; Florath, Ines (2009)
Background and Aim: Early and mid-term clinical outcomes after aortic valve replacement (AVR) with stentless bioprostheses in a large cohort of patients are presented. Methods: Between April 1996 and November 2005, 1014 patients underwent AVR with the stentless Medtronic Freestyle bioprosthesis, with 168 using the full-root technique. The mean age was 73 ± 3 (range: 20 to 90) years. Follow-up included 2953 patient-years and was 95% complete for adverse events. Results: Operative mortality was 3.4% (N = 34). Overall survival was 46 ± 9% at nine years and similar to age- and gender-matched German general population. Freedom from prosthetic valve endocarditis, major bleeding, neurological events, and reoperation after nine years was 97 ± 6%, 92 ± 7%, 70 ± 16%, and 92 ± 9%, respectively. Freedom from structural valve deterioration was 97 ± 5% at 9 years. During the learning phase, mean transprosthetic gradients of 23.5 ± 3.0 mmHg and 24.8 ± 3.1 mmHg were observed for valve sizes 21 and 23 mm, respectively, 10 days after subcoronary implantation in 1997, which could be lowered to 16 ± 2.1 mmHg and 14.9 ± 0.9 mmHg in 2005, respectively, with increasing experience of the surgeons. During the follow-up period, mean gradients dropped on average by 15 mmHg in patients presenting higher gradients at discharge. Conclusions: The Freestyle stentless bioprosthesis showed encouraging midterm durability with low rates of valve-related morbidity, and can be safely implanted without increased operative risk even during the learning phase. Special training of the surgeons is recommended to achieve optimal hemodynamic performance. © 2008 Wiley Periodicals, Inc.